2015
DOI: 10.1097/cnq.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

The Older Adult Experiencing Sepsis

Abstract: Sepsis is a potentially fatal response to infection affecting patients across the life span. Sepsis can progress from systemic inflammatory response to severe sepsis and septic shock if not recognized promptly and managed effectively. Risk factors for sepsis include age, gender, the presence of invasive devices (eg, urinary catheters), and chronic medical conditions (eg, chronic obstructive pulmonary disease). Sepsis awareness is essential and includes identification of population-focused risk factors, recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Equally relevant is that sepsis occurs disproportionately in older adults with more than 50% of cases occurring in those aged 65 and older . In addition, the outcomes of sepsis are worst in older adults, with higher rates of mortality, organ dysfunction, cognitive impairment, permanent disabilities, and long‐term institutionalization …”
Section: Introductionmentioning
confidence: 99%
“…Equally relevant is that sepsis occurs disproportionately in older adults with more than 50% of cases occurring in those aged 65 and older . In addition, the outcomes of sepsis are worst in older adults, with higher rates of mortality, organ dysfunction, cognitive impairment, permanent disabilities, and long‐term institutionalization …”
Section: Introductionmentioning
confidence: 99%
“…The later comprise the use of invasive devices (intravascular catheters, endotracheal tubes, indwelling bladder catheters, etc. ), immobilization and exposition to nosocomial flora [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…It is known that the incidence of sepsis and the rate of hospitalization due to sepsis increase with age. Englart et al reported that there was an increase in hospitalization rates due to sepsis between the years 1997 and 2011 and that this increase was 3 times higher in the ages between 65 and 84 and 2 times higher in ages ≥85 (9). Angus et al demonstrated that the incidence of sepsis was 0.2/1000 in the pediatric age group and 26.2/1000 in individuals ≥85 years of age, which was almost 100 times higher compared to that found in children (10).…”
Section: Discussionmentioning
confidence: 99%